Reconstruction of Past Glacier Changes with an Ice-Flow Glacier Model: Proof of Concept and Validation - Eis, Julia; van der Laan, Larissa; Maussion, Fabien; Marzeion, Ben (Frontiers in Earth Science, 2021)
Estimations of global glacier mass changes over the course of the 20th century require automated initialization methods, allowing the reconstruction of past glacier states from limited information. In a previous study, we developed a method to initialize the Open Global Glacier Model (OGGM) from past climate information and present day geometry alone. Tested in an idealized framework, this method aimed to quantify how much information present-day glacier geometry carries about past glacier states. The method was not applied to real world cases and therefore the results were not comparable with observations. This study closes the gap to real world cases by introducing a glacier-specific calibration of the mass balance model. This procedure ensures that the modeled present day geometry matches the observed area and that the past glacier evolution is consistent with bias-corrected past climate time series. We apply the method to 517 glaciers, spread globally, for which either mass balance observations or length records are available, and compare the observations to the modeled reconstructed glacier changes. For the validation of the initialization method we use multiple measures of reconstruction skill (e.g. MBE, RMSE, correlation). We find that the modeled mass balances and glacier lengths are in good agreement with the observations, especially for glaciers with many observation years. These results open the door to a future global application.